2020
DOI: 10.1177/2473011420959651
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Study of the Cuboid and Its Ligamentous Attachments and Its Implications for a Cuboid Osteotomy

Abstract: Background: Lateral column lengthening (LCL) for flexible flatfoot is an effective surgery with powerful correction of deformity because it tightens only the lateral third of the long plantar ligament (LPL). However, LCL has been associated with joint damage at the osteotomy site and loss of foot flexibility owing to joint fixation. We focused on the cuboid and investigate a novel anatomical LCL osteotomy site that effectively tightens the LPL without damaging any joints. Methods: We studied 24 feet of 12 cada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Tazaki et al suggested that cuboid osteotomy would be useful in lengthening the lateral column for flat foot correction. The osteotomy line on the cuboid should pass 4 mm from the calcaneocuboid joint laterally due to the attachment of the long plantar ligament, and on the medial side, 6 mm from the cuboid-metatarsal joint due to the presence of a navicular facet proximal to the cuneocuboid joint [7]. The presence or absence of a navicular facet depends on the type of gait pattern, weight transmission, and environmental and genetic factors.…”
Section: Ecto-cuneiform and Navicular Articular Facetmentioning
confidence: 99%
See 1 more Smart Citation
“…Tazaki et al suggested that cuboid osteotomy would be useful in lengthening the lateral column for flat foot correction. The osteotomy line on the cuboid should pass 4 mm from the calcaneocuboid joint laterally due to the attachment of the long plantar ligament, and on the medial side, 6 mm from the cuboid-metatarsal joint due to the presence of a navicular facet proximal to the cuneocuboid joint [7]. The presence or absence of a navicular facet depends on the type of gait pattern, weight transmission, and environmental and genetic factors.…”
Section: Ecto-cuneiform and Navicular Articular Facetmentioning
confidence: 99%
“…The morphology and morphometric analysis of cuboid bone is crucial for designing the prosthesis for foot and ankle reconstructions and in finite element modeling (FE) or statistical shape modeling (SSM) [5,6]. Knowledge about cuboid morphometry can assist surgeons in understanding the basics behind lateral foot syndrome, which includes chronic pain, trauma, fracture dislocation, and joint instability associated with cuboid bone, and in cuboid osteotomy for lateral column lengthening in flatfoot deformity [7]. It also provides knowledge about the evolution of human bipedalism and the kinematics of the cuboid bone with adjacent tarsal and metatarsal bones, which can help during prosthesis design.…”
Section: Introductionmentioning
confidence: 99%